Odpowiedź :
Wzór na pole trapezu: P=(a+b)*h/2
P=(a+b)*h/2 /*2
2P=(a+b)*h /:h
2P/h=a+b
2P/h -b=a -pierwsza podstawa
P=(a+b)*h/2 /*2
2P=(a+b)*h /:h
2P/h=a+b
2P/h -a=b - druga podstawa
P=(a+b)*h/2 /*2
2P=(a+b)*h /:h
2P/h=a+b
2P/h -b=a -pierwsza podstawa
P=(a+b)*h/2 /*2
2P=(a+b)*h /:h
2P/h=a+b
2P/h -a=b - druga podstawa
p=(a+b)*h
-----------
2
2p=(a+b)*h
2p=ah+bh /:ah
2p
----- =bh /h
ah
(2p:ah):h=b
na podstawie tego tak samo b
-----------
2
2p=(a+b)*h
2p=ah+bh /:ah
2p
----- =bh /h
ah
(2p:ah):h=b
na podstawie tego tak samo b